The Moral Importance Of Humanity And Patriotism In Chistiya And Kubraviya - Razzoqov Qosimbek Quvanovich (International Journal on Orange Technologies, 2021)
The article reflects the teachings of Sufism, its definitions, the views of the saints of the Chistiya and Kubraviya sects on humanity and patriotism, as well as the essence of the principles of humanity and patriotism, as well as the views expressed by the President